Public Sector Accountability : A Comparative Perspective. - abolhasan faghihi (مطالعات مدیریت بهبود و تحول, 2001)
The subject of this article  is the issue of accountability in public sector.  It aims  to define  and conceptualize  accountability and present a typology to be used  for comparison among contemporary  political and administrative systems. To  this end, the article  intends to  formulate  a model  through  which systems of accountability in countries such  as Britain and United States as well as Pakistan, Bangladesh  and Zambia  will be examined. This analysis, will reveal  a measure of effectiveness of the  above - mentioned systems. It also, suggests and analytical framework for comparative studies on administrative behavior.